Transformações na indústria sucroalcooleira brasileira no início do século XXI: das famílias aos acionistas - Mundo Neto, Martin (2012)
Over the last years, many companies have joined the Brazilian capital market. This movement would be said to have unfolded the institutional changes that occurred in Brazil during the last decade of the twentieth century, especially, the privatization process of a set of large Brazilian State-owned enterprises, the new law of public corporations and the new rules adopted in the Sao Paulo Stock Exchange Market. Concomitantly, the Brazilian sugarcane industry has undergone several transformations. If until the decade of 1990, the hegemony was characterized by national groups under the control of traditional families, the intensification of the mergers and acquisitions operations with a significant participation of international investors has, however, modified this space. The empirical data point out the capital concentration in the industry, notably by means of mergers and acquisitions as well as the business restructuring anchored on the notion of shareholder value and corporate governance. This process could also be understood as part of the financialization process which has been diffused in the Brazilian society. Here, our focus will be highlighted on the participation of the representatives from the risk-capital industry, notably the BNDES Participations, a subsidiary of the National Development Bank (BNDES), which has played a major role in the diffusion of a new control conception for the Brazilian industries in general. Among the main Sugarcane groups considered, a significant increase could be observed on the part of international investors as well as huge national economic groups that were not previously present in the industry.